(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The present paper discusses the criminal lawsuit filed by the council authorities in the city of San José de Cúcuta in 1799 against some slaves and their owner for putting on fire the ranches occupied by some peasants on the lands of the landowner. The aim of the study is to analyze how these slaves converted into bandits when serving their master, their motivations to commit the crime and the conflictive conditions behind it.